The Experimental Study on the continuous Anti-bacterial Potency of Coptidis rhizoma extract on Cultivation of Staphylococcus species(S. aureus, S. epidermidis) - Seo, Hyeong-Sik (Korean Pharmacopuncture Institute, 2007)
Objectives This experimental study was performed to investigate the continuous anti-bacterial potency of Coptidis rhizoma extract on cultivation of Staphylococcus species(S. aureus, S. epidermidis) that induce eye disease. Methods Minimal inhibitory concentration(MIC) was measured by dropping to 50ul diluted Coptidis rhizoma extract(100%, 10%, 1%, 0.1%) on S. aureus, S. epidermidis that were cultivated from 2 to 6 days. Anti-bacterial potency was measured by the size of inhibition zone with change of volume(20ul, 30ul, 40ul, 50ul). Results 1. Anti-bacterial potency of Coptidis rhizoma extract on S. aureus was appeared in 100%, 10% and was the same as anti-bacterial potency of 2 days and 6 days. Anti-bacterial potency with change of volume(100%) was increased in propotion to increase volume on all samples. Anti-bacterial potency with change of volume(10%) was increased in propotion to increase volume on all samples except . Anti-bacterial potency of Coptidis rhizoma extract on S. aureus was appeared continuous. 2. Anti-bacterial potency of Coptidis rhizoma extract on S. epidermidis was appeared in 100%, 10% and was the same as anti-bacterial potency of 2 days and 6 days. Anti-bacterial potency with change of volume(100%) was increased in propotion to increase volume on all samples 20ul. Anti-bacterial potency with change of volume(10%) was appeared in . Anti-bacterial potency of Coptidis rhizoma extract on S. epidermidis was appeared continuous. Conclusions Anti-bacterial potency of Coptidis rhizoma extract on cultivation of S. aureus & S. epidermidis was showed continuous.